Interactional fairness as a mediator between merit-based pay management and organizational commitment - Mohd Ridwan Abd Razak (Tanjong Malim, 2021)
Interactional fairness as a mediator between merit-based pay management and organizational commitment by Mohd Ridwan Abd Razak